The ‘de novo’ DNA methyltransferase Dnmt3b compensates the Dnmt1-deficient intestinal epithelium - Elliott, Ellen N (eLife, 2016)
Dnmt1 is critical for immediate postnatal intestinal development, but is not required for the survival of the adult intestinal epithelium, the only rapidly dividing somatic tissue for which this has been shown. Acute Dnmt1 deletion elicits dramatic hypomethylation and genomic instability. Recovery of DNA methylation state and intestinal health is dependent on the de novo methyltransferase Dnmt3b. Ablation of both Dnmt1 and Dnmt3b in the intestinal epithelium is lethal, while deletion of either Dnmt1 or Dnmt3b has no effect on survival. These results demonstrate that Dnmt1 and Dnmt3b cooperate to maintain DNA methylation and genomic integrity in the intestinal epithelium. DOI: http://dx.doi.org/10.7554/eLife.12975.001